Analisis Faktor Penghambat Akuntabilitas Pengelolaan Barang Milik Negara Dan Daerah: Systematic Literature Review - M. Ramadhan; M. Riva Bintang Pratama; Ahmad Muflih Makarim; M. Abdilah Maghfiro; Rika Henda Safitri (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2026)
The management of State and Regional Property (BMN/BMD) is a vital component in realizing good governance, yet its implementation in the field remains fraught with various obstacles. This study aims to identify and analyze in-depth the factors hindering the accountability of public asset management. The approach employed is a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol. A literature search was conducted via Google Scholar and Garuda databases, which ultimately selected 15 primary articles from a total of 80 documents identified at the initial stage. The synthesized results indicate that accountability barriers originate from four main dimensions. First, the low proficiency and capability of management personnel, which is further exacerbated by inappropriate job placements. Second, disruptions in information technology infrastructure and a lack of digital literacy among staff. Third, the absence of complete and valid ownership documentation, rendering government assets vulnerable to legal disputes. Fourth, the limited availability of maintenance funds and external interventions that bypass standard regulations. This study concludes that improving asset governance requires comprehensive resolution steps, including enhancing employee proficiency, strengthening legal security, decisive leadership, and providing adequate technological infrastructure.